Magnetic nanocomposites based on borate glasses doped with Fe and Mn - Edelman, I.S.; Ivantsov, R.D.; Ivanova, O.S.; Bayukov, O.A.; Zaikovskii, V.V. (Functional Materials, 2006)
Magnetic properties, including magneto-optical Faraday Effect (FE), have been investigated in potassium-aluminum-boron glasses doped with iron and manganese oxides. The formation of magnetic nanoparticles has been proved using high resolution electron microscopy. A wide variety of particle size, shape, structure, and distribution in the matrix has been observed depending on the technological conditions. The narrow region of conditions has been established providing formation of almost ideal manganese ferrite single crystals of about 40 nm size distributed rather homogeneously in the matrix. Therefore, the glasses can be considered as a nano-composite material. Thanks to the low concentration of paramagnetic elements, the glasses kept the optical transparence and demonstrated high FE in the infrared and a part of the visible spectral regions, thus making it possible to develop a new magneto-optical material for the 1.0-1.5 μm spectral region.